A cooperative governance framework for sustainable digital transformation in construction: The role of digital enablement and digital strategy - Ahmed Mohammed Shirwa; Abdiqani Muse Hassan; Abdiqani Qorane Hassan; Muslum Kilinc (Results in Engineering)
Sustainable digital transformation is not just a technological shift but a comprehensive cultural and operational change for more efficient, effective, and sustainable processes. Existing studies neglect the importance of stakeholder collaboration in achieving these goals. This study addresses this gap by developing a Cooperative Governance Framework designed to align technological advancements with environmental and social objectives. Drawing on institutionalism and political systems theory, the study identifies five aspects and 36 criteria, using a hybrid approach of the Fuzzy Delphi Method and Fuzzy Decision Making Trial and Evaluation Laboratory. The study aims to identify and validate critical drivers of sustainable digital transformation in the construction industry, explore their interrelationships, and propose a comprehensive governance framework. The results validated 26 criteria and highlighted core drivers as digital enablement and digital strategy. Key practical findings emphasize the importance of digital infrastructure, competence, quality control, and business strategy integration for effective transformation.